Optimising the amounts of microsilica and nanosilica in concrete using response surface method - Manzoor, Z.; Barbhuiya, Salim; Shaikh, Faiz; Cheema, D. (2017)
The use of microsilica (MS), a by-product of smelting process in the silicon and ferrosilicon industry, to replace some part of cement in concrete has now become very popular in construction industry. Nanosilica (NS), on the other hand, is also known to improve various properties of concrete. However, NS is still a relatively new material, and its price is much higher compared to that of MS. Therefore, from economy point of view, it is better to use NS in combination with MS. In this research the amount of MS and NS was optimized using Response Surface Method (RSM). Two independent variables (MS and NS content) were evaluated in three levels—minimum, maximum and midpoint of the experimental domain. The replacement levels for MS were 5% and 10% (by cement wt.) and those for NS were 1% and 2% (by cement wt.). Nine concrete mixes were prepared and three responses (compressive strength, RCPT and sorptivity) were measured.